PENGARUH KINERJA KEUANGAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN YANG DIMODERASI VARIABEL KEPEMILIKAN MANAJERIAL - Ningsih, Wirdia; Sulastiningsih (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2024)
This study aims to examine the effect of financial performance and capital structure on firm value with managerial ownership as a moderating variable. This research uses a quantitative approach with secondary data taken from the financial statements of companies officially published on the Indonesia Stock Exchange (IDX). The sample consists of 12 mining sector companies selected using a purposive sampling technique. Data analysis was performed using multiple linear regression and Moderated Regression Analysis (MRA). The results showed that financial performance has a significant positive effect on firm value, capital structure has no significant effect on firm value, managerial ownership has no significant effect on firm value, managerial ownership cannot moderate the effect of financial performance on firm value, and managerial ownership cannot moderate the effect of capital structure on firm value.